Association between local food policy council coverage and longitudinal household food insufficiency during COVID-19, stratified by race, ethnicity, and income - Larissa Calancie; Yongyi Pan; Karen Bassarab; Kristen Cooksey Stowers; Anne Palmer; Misha Eliasziw (PLoS ONE, 2026)
Many local food policy councils (FPCs) worked to increase food access during the COVID-19 pandemic. Our objective was to determine whether households living in states with higher FPC coverage were less likely to experience food insufficiency during COVID-19 compared to households in states with lower local FPC coverage, and to analyze associations by race, ethnicity, and household income. We used a modified Poisson regression approach to estimate the prevalence of household food insufficiency in states with high and low FPC coverage as of 2020, adjusting for age and gender of the survey respondent, and percent of the state’s population living in a rural area (N = 1,909,647). Longitudinal food insufficiency was measured via the US Census Household Pulse Survey (May 2020 – May 2023). Lower income households in states with low FPC coverage were more likely to experience food insufficiency during the pandemic than households in states with high FPC coverage (food insufficiency prevalence ratio: 1.05, 95% CI 1.04–1.07, p < 0.001). Lower FPC coverage was associated with significantly more food insufficiency among lower-income non-Hispanic Black (1.05, 95% CI 1.02–1.09, p = 0.003) and white households (1.02, 95% CI 1.00–1.04, p = 0.01). Presence of FPCs may have been a protective factor against food insufficiency for low-income Black and white households during the COVID-19 pandemic. Local FPCs may have potential for promoting resilience and racial equity within food systems.